Are there associations between religious affiliation and drive for muscularity? A cross-sectional survey of young Muslim women, Christian women and atheist women from Germany - Wilhelm, Leonie; Hartmann, Andrea S.; Becker, Julia C.; Waldorf, Manuel; Vocks, Silja (BMC women's health, 2020)
Background Over the last 20 years, society’s perception of the ideal female body size in Western cultures has changed from thin to athletic, and many women practice sports to achieve well-toned bodies. However, to date, no study has investigated whether Muslim women who live in a Western country and veil their bodies strive for lean or muscular bodies too. The current cross-sectional survey therefore addressed this question. Methods Veiled Muslim women ( n = 70), unveiled Muslim women ( n = 50), Christian women ( n = 79), and atheist women ( n = 68) living in Germany answered several questionnaires assessing engagement in sports, body appreciation, and drive for leanness and muscularity. Univariate and multivariate analyses were conducted to compare the four groups. Results The results of univariate and multivariate analyses showed that Muslim women engaged less in sports and veiled Muslim women reported higher body appreciation than did Christian and atheist women. Although the groups did not differ significantly in drive for muscularity, Muslim women showed lower levels of drive for leanness than did Christian and atheist women. Conclusion Given that Muslim women engaged less in sports and strived less for a lean body compared to Christian and atheist women, a well-toned body might be less important for them. Nevertheless, as being active is beneficial for general health, barriers that prevent Muslim women from engaging in sports should be diminished.